Pitted stones in the Acheulean from Olduvai Gorge Beds III and IV (Tanzania): A use-wear and 3D approach. Issue 145 (August 2020) - Arroyo, Adrián; de la Torre, Ignacio
Abstract: The archaeological sequence of Olduvai Gorge Beds III and IV is essential for the study of the evolution of the African Acheulean between ∼1.3 Ma and 0.6 Ma. However, no further reexaminations of the lithic assemblages have been published after Mary Leakey's original work. In this article, we present an analysis of a part of these collections, with an emphasis on the microscopic and spatial analysis of percussive marks in the so-called pitted stones. To investigate the function of pitted stones and understand the formation process of depressions on lava cobbles, archaeological pitted stones were compared with experimental tools used in bipolar knapping, nut-cracking, and flake-splitting activities. Our results demonstrate that features of pitted stones remained homogeneous across Beds III and IV assemblages, with depressions preferentially located on the central areas of the tools and similar use-wear traces inside such depressions. Comparisons with the experimental collection demonstrate that these depressions are rapidly formed when splitting flakes, resulting in elongated morphologies similar to those documented in the archaeological tools. Our results are discussed within the context of other archaeological and nonhuman primate assemblages to further explore the function of pounding activities in which pitted stones could have potentially been involved. Highlights: We present the first microscopic analysis of pitted stones from the Acheulean Beds III and IV at the Olduvai Gorge. The microscopic and geographic information system results show a consistency on their function through the stratigraphic sequence. The results are compared with other experimental and archaeological assemblages. Bipolar knapping and flake splitting are the most likely activities involved in their use.